A new species of Oreosaurus (Squamata: Gymnophthalmidae) from the Turimiquire Massif, northeastern Venezuela - Rivas, Gilson A.; Nunes, Pedro M. Sales; Baran, Agnieszka; Jowers, Michael J.; Smith, Eric N.; Hernández-Morales, Cristian; Schargel, Walter E. (Zootaxa, 2021)
We describe a new species of gymnophthalmid lizard, Oreosaurus bisbali sp. nov., from the Turimiquire Massif in northeastern Venezuela. It is one of three reptile species known to be endemic to the region and the fifth species of Oreosaurus from Venezuela. It can be distinguished from all congeners by a combination of rectangular dorsal scales at midbody, having two scales separating femoral pores medially, and lacking a nasoloreal suture. The new species is likely to be restricted in distribution to the highlands of the Turimiquire Massif, which have been significantly degraded by agriculture.